Tema, rimas y leyendas de Gustavo Adolfo Bécquer - Paz Quesquen, Ray Franco (2019)
The present work of professional sufficiency is structured in three parts, which are related to each other, whose thematic axis are the characteristics and romantic lyrical literary forms of the Rhymes and legends of Gustavo Adolfo Bécquer. In addition to two livelihoods, one pedagogical and another scientific. Within this learning session, competencies, skills and indicators specified, as well as the parties with their respective activities to develop. In the pedagogical support, everything, corresponding to a learning session is specified defining concepts such as society, learning, education, skills, abilities, strategies, evaluation, etc. In addition to the learning theories that it will be used for its execution._x000D_ Within the learning session the competence, capacities and indicators to be treated for said session are specified, as well as the parties with their respective activities to be developed. In the pedagogical support, everything corresponding to a learning session is specified, defining concepts such as: society, learning, education, skills, abilities, strategies, evaluation, etc. In addition to the learning theories that will serve for its execution._x000D_ In what corresponds to the theoretical support, this is focused on defining the romantic literary characteristics of the Rhymes and legends, adding each of these qualities, strategies and examples of analysis so that it is easy to motivate, understand and understand for the students with whom He goes to work.